Двухграничные задачи для случайного блуждания - Ежов, И.И.; Каданков, В.Ф.; Каданкова, Т.В. (Український математичний журнал, 2007)
Розв'язано основні двограничні задачi для випадкового блукання. Наведено генератриси сумісних розподілів: моменту першого виходу блукання з інтервалу i величини перестрибу границі в момент виходу, моменту першого входження блукання в інтервал та його значення в момент входження. На геометрично розподіленому часовому проміжку отримано розподіли: supremum'a, infimum'a та значення блукання, числа перетинів інтервалу зверху i знизу. Наведено приклади застосування отриманих результатів до випадкового блукання з показниково розподіленими в один бік стрибками. We solve main two-boundary problems for a random walk. The generating function of the joint distribution of the first exit time of a random walk from an interval and the value of the overshoot of the random walk over the boundary at exit time is determined. We also determine the generating function of the joint distribution of the first entrance time of a random walk to an interval and the value of the random walk at this time. The distributions of the supremum, infimum, and value of a random walk and the number of upward and downward crossings of an interval by a random walk are determined on a geometrically distributed time interval. We give examples of application of obtained results to a random walk with one-sided exponentially distributed jumps.